Assessing Early Indicators of Tolerance and Stool Microbiome in Infants Receiving Formula with Added Lactobacillus rhamnosus GG (LGG). (29th May 2020) - Chichlowski, Maciej; Harris, Cheryl; Wampler, Jennifer; Berseth, Carol Lynn
Abstract: Objectives: To evaluate stool microbiome and calprotectin in infants receiving partially hydrolyzed protein formula with or without Lactobacillus rhamnosus GG (LGG). Methods: In this single-center, double-blind, controlled, parallel, prospective study, infants (14-28 days of age) experiencing crying/fussing often associated with infantile colic were randomized to receive one of two formulas over a 21-day feeding period: marketed partially hydrolyzed (PH) cow's milk-based infant formula (PH: n, 35) or a similar formula with added LGG (PH-LGG: n, 36). Stool samples were collected at Baseline and Study End (Days 19–21). Stool calprotectin (μg/g) was determined by immunoassay and analyzed (Kruskal-Wallis). LGG colonization was determined by qPCR analysis.16S rRNA gene sequencing was performed (Illumina MiSeq) and QIIME operational taxonomic units (OTUs) were assigned (Greengenes database). Alpha and beta diversity were analyzed by study group and time point. Results: A significantly higher abundance of LGG was demonstrated at Study End vs Baseline for the PH-LGG ( P  < 0.001) but not PH group ( P  = 0.89). Alpha diversity (Shannon) was significantly higher at Study End vs Baseline in the PH group ( P  = 0.014). By Study End, members of Phylum Firmicutes were significantly higher ( P  = 0.002) and Family Enterococcaceae were significantly lower ( P  = 0.02) in the PH-LGG group. No group differences in stool calprotectin (median) were detected at Baseline (PH: 12.4, n = 26; PH-LGG: 13.9, n = 30) or Study End (PH: 12.4, n = 30; PH-LGG: 12.9, n = 30). Conclusions: In infants receiving a partially hydrolyzed protein formula with added LGG over a 21-day feeding period, LGG was established in the stool microbiome. Associated potentially beneficial bacterial taxa were also increased. Funding Sources: Mead Johnson Nutrition.